Perancangan Sistem Informasi Penggajian Karyawan Berbasis Web Menggunakan Rapid Application Development (Studi Kasus : PT. Praktisindo Media Cipta) - Muhammad Ghozi; Rinna Rachmatika (CV. Multi Kreasi Media, 2023)
PT. Practicalindo Media Cipta is a business engaged in services, sales of hardware, software, maintenance and maintenance of computers. At present the company's data processing has implemented a computerized payroll system using Ms.Excel but for attendance at the company it is still not computerized, namely by using a paper attendance form provided by the administration every day so that the data processing experiences problems and the occurrence of process errors such as salary calculations, payroll deductions and payroll reports. Things that often happen mistakes that can harm employees. The designed information system is expected to make it easier for companies to calculate employee salaries and reduce calculation errors and data validation. This information system design method uses the RAD (Rapid Application Development) method with the SDLC model which is able to create a system in stages so that it becomes an alternative method chosen in designing this application. The results of the research that has been done can facilitate the management of attendance data, record admin and payroll employees quickly and on time.